Groundswell : winning in a world transformed by social technologies - Li, Charlene; Bernoff, Josh. (Boston, Mass. : Harvard Business Press, 2008)
"In Groundswell, two top analysts from Forrester Research show you how to turn the force of customers connecting to your own advantage. With twenty-five vivid cases from around the world--from health care to retail to consumer goods to business services--Li and Bernoff show how leading companies are gaining insights, generating revenue, saving money, and energizing their own customers. Whether you're in marketing, research, support, sales, development, or even running the whole enterprise, there's targeted advice here for you, backed up with real-world ROI to prove it works"--Page 2 of cover.
Understanding the groundswell -- Why the groundswell--and why now? -- Jujitsu and the technologies of the groundswell -- The social technographics profile -- Tapping the groundswell -- Strategies for tapping the groundswell -- Listening to the groundswell -- Talking with the groundswell -- Energizing the groundswell -- Helping the groundswell to support itself -- Embracing the groundswell -- The groundswell transforms -- How connecting with the groundswell transforms your company -- The groundswell inside your company -- The future of the groundswell.
Includes bibliographical references (pages 247-263) and indexes.
Keywords: Online social networks -- Economic aspects; Information society -- Economic aspects; Internet; Marketing; Online social networks -- Economic aspects; Information society -- Economic aspects; Information society -- Economic aspects